Cerebrospinal fluid findings in patients with neurological manifestations in post-COVID-19 syndrome - Boesl, Fabian; Goereci, Yasemin; Gerhard, Ameli; Bremer, Benno; Raeder, Vanessa; Schweitzer, Finja; Hoppmann, Uta; Behrens, Janina; Bellmann-Strobl, Judith; Paul, Friedemann; Wildemann, Brigitte; Jarius, Sven; et al. (Journal of neurology, 2024)
Information on cerebrospinal fluid (CSF) findings in patients with neurological manifestations in post-COVID-19 syndrome is scarce.
Online veröffentlicht: 24 November 2023
Gesehen am 05.04.2024